On the Blowup for the 3D Axisymmetric Incompressible Chemotaxis-Euler Equations - Shangyong An; Qian Zhang (Journal of Function Spaces)
In this paper, we investigate the 3D incompressible chemotaxis-Euler equations. Taking advantage of the structure of axisymmetric fluids, we establish the blowup criterion of the system using the Fourier localization method.